The Impact of the Covid-19 Pandemic on the Income of Butchers Broilers at Traditional Market in Sidikalang District - E. Mirwandhono; T.V Sari; M. A. Hussein; Angkat, S.K.M (Talenta Publisher, 2022)
The covid 19 pandemic has negatively impacted various sectors, including livestock product trading. This study aims to find out how much income impact due to covid 19 pandemic on broiler meat traders at the Traditional Market, Sidikalang District, and understand the marketing strategies carried out by traders during the Covid-19 pandemic. The research was conducted at the Traditional Market, Sidikalang District, in September 2021. The sample determination used a saturated sample technique ( total sampling ), where all population members were used as samples because the population used was relatively small. Data analysis was carried out by calculating the income of traders before and during the Covid-19 pandemic and describing the data generated from the impact felt during the Covid-19 pandemic. The results showed decreasing butchers' gain after the emergence of the Covid-19 outbreak. The highest revenue from the middle business group reached IDR 5,025,000 or around 31.1%, and the lowest income difference in the small business group got IDR 2,480,000 or about 24.8% after the Covid-19 pandemic. The provision of policies during the Covid-19 pandemic by limiting operational time and market capacity by complying with health protocol recommendations and assisting in the form of money and necessities to traders are some of the government's roles during the Covid-19 pandemic for broiler chicken traders. The strategy carried out by traders to increase sales during the Covid-19 pandemic is to continue to supply excellent and fresh broiler chicken, give discounted prices, offer a delivery system, as well as promote merchandise through social media.